Translation Strategy of Hyperbole in Mickey and Donald: The Search of Zodiac Stone from English to Indonesian - Gina Aulia; Hayatul Cholsy (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Hyperbole in comic translation presents a challenge for translators as comics incorporate various cultural elements from the source language. Making translators carefully consider these cultural aspects to ensure accurate and culturally appropriate translations.  The comic Mickey and Donald: The Search of Zodiac Stone is considered as the humor comic category because it combines numerous elements of hyperbole and various cultural aspects, utilizing informal and casual language. The current study aims to identifies and analyze strategies used to translate hyperbolic expression from English to Indonesian. Translation strategy from Baker and Celotti are used for the current study. The method used in this study is a qualitative descriptive approach. Mixed translation strategy or a combination of translation strategies mostly used when translating the hyperbole. Overall, mixed translation strategies were employed to render hyperbolic expressions primarily due to the character and spatial constraints inherent in comic translation.